Computação reversível fotônica: uma proposta de uma porta Toffoli usando QND para qubits baseados em polarização e suas aplicações - Policarpo, Samy Clever (2023)
Reversible photonic computing is a promising research field that seeks to develop computers that can perform calculations without loss of information by means of the controlled manipulation of light. Reversibility is an important property of a computational system, as it allows the system to be restored to its initial state after the calculation. This can be useful for applications such as cryptography, security, and image processing. This work presents a theoretical optical apparatus (cS) for polarization qubits based on quantum nondemolition measurements (QND) which through analytical and comparable calculations, presented an efficiency greater than 90% that is capable of performing the Toffoli gate function. The proposed optical system is configurable, based on prior configuration and combination, and reversible AND, NAND, Toffoli, CNOT, Peres, Fredkin, HNG, and ALG gates can be obtained, as well as any other reversible gate based on C n+1 -NOT gates. The cS system can be configured to function as a sequential binary comparator and the same can be used as a Bell state generator.